ENGLISH EDUCATION STUDENTS’ MOTIVATIONAL STRATEGIES IN ACQUIRING PUBLIC SPEAKING SKILLS BASED ON THE ACTIVITY THEORY PERSPECTIVE - Aplonia Nelci Ke Lomi; Markus Budiraharjo (IKIP Siliwangi, 2022)
From the perspective of Activity Theory (AT), this study demonstrates the existence of motivational strategies and influencing factors acknowledged by English Education students to acquire public speaking skills. Subject, object, outcome, tools, community, rules, and division of labor are all components of Activity Theory (AT). This mixed-method study examines the learning experiences of English Education students in relation to AT components. This study included 16 English Education students. The researchers collected data using questionnaires and interviews. The study found that students used a variety of strategies. They were basically forcing themselves to speak, practicing with their peers, and self-practicing (division of labor). The students reported their happiness with the public speaking class learning process (object). The lecturer's varied learning sources also helped the students succeed in class (tools). Their classmates and lecturer aided and supported them positively (community . There were their obligations in the class were made to manage the class (rules). As a result, English Education departments should promote students' motivation in mastering language skills. Future researchers are encouraged to study language skills acquired by language students in a broader context and with more participants. Keywords: English Education, Public Speaking Skills, Activity Theory Perspective